"The secret rapport between photography and philosophy" considering the South African photographic apparatus through Veleko, Rose, Goldblatt, Ractliffe and Mofokeng - Mountain, Michelle Fiona (Rhodes University, Faculty of Humanities, Department of Fine Art, 2010)
This thesis is an attempt at understanding South African photography through the lens of Nontsikelelo "Lolo" Veleko, Tracy Rose, David Goldblatt, Jo Ractliffe and Santu Mofokeng. Through the works discussed this thesis intends to unpack photography as a complex medium similar to that of language and text, as well as attempt to understand how exploring South African experiences and spaces through the lens of photography shapes and mediates them. Furthermore it also attempts to understand how these experiences and spaces conversely affect the discourse of photography or at the very least our perception of it. Through these photographers and their works it is hoped that ultimately the interconnected relationship of exchanging codes that takes place between photography and society will be highlighted. The example of connectivity or dialogue I believe exists between the medium of photography and the physical/social and psychological spaces it photographs will be mediated through Deleuze and Guattari"Ÿs conception of "the wasp and the orchid" where "the wasp becomes the orchid, just as the orchid becomes the wasp...an exchanging or capturing of each other"Ÿs codes" . Other theorists I will be looking at include Vilém Flusser, focusing in particular on his book Towards a Philosophy of Photography, as well as Susan Sontag, Roland Barthes and others. The main aims and objectives of this thesis are to understand the veracity of the documentary image and whether or not the image harbours any objective truth, as well as whether truth, if it can truly be said to exist in the world, resides between the camera and the seen world. This dichotomy is further complicated by the matter of subject-hood and technical and philosophical understandings of the camera as an apparatus. At no point do I aim to be conclusive, rather it is hoped that by developing the dynamic tension between the theory and the image world that I will be able to bring fresh insight into the reading of a changing South African condition and the subject position of the photographer in relation to this condition.
Keywords: Veleko, Nontsikelelo; Rose, Tracy; Goldblatt, David; Ractliffe, Jo 1961-; Mofokeng, Santu, 1956-; Photographers -- South Africa; Photography -- Philosophy; Photography -- Social aspects -- South Africa; Apartheid in art; Documentary photography -- South Africa; Space (Art) -- South Africa; South Africa -- Social conditions